Evolusi bahasa dalam kalangan masyarakat Semai: Suatu kajian kes di Kampung Sungai Ruil, Cameron Highlands - Yaakub, Yusniza; Ahmad, Faizah; Mansor, Nasariah (2011)
Semai tribe has the highest population among the 18 indigenous tribes in Malaysia. Most of them settle around the Titiwangsa Mountain Range which encompasses an area of the Middle and South Perak, and West Pahang.They use Semai language which was passed down from generation to generation as their first language.It is a well known fact that the indigenous tribes have unique culture and traditions.Being isolated geographically has led them to strongly retain and belief in their culture and traditions. However, the Semai tribe in Kampung Sungai Ruil on the outskirts of Tanah Rata, Cameron Highlands is an exception. The village is a new structured settlement and most of the villagers belong to the Semai tribe. As a result of modernization, they have been influenced by globalization and their language and culture have undergone significance evolution. This is due to its location which is in the suburbs and to the existence of a golf course adjacent to their villages which have attracted the public, especially foreign tourists to frequent the villages.This working paper examines the factors that have led to the evolution of the language and culture of the Semai community in Sungai Ruil, Cameron Highlands, Pahang.